Simultaneous determination of quinoxaline‐1, 4‐dioxides in feeds using molecularly imprinted solid‐phase extraction coupled with HPLC. Issue 2 (10th December 2012) - He, Qianqian; Fang, Binghu; Su, Yijuan; Zeng, Zhenling; Yang, Jianwen; He, Limin; Zeng, Dongping
<x xml:space="preserve">Abstract</x> A simple, selective, and reproducible molecularly imprinted SPE coupled with HPLC method was developed for monitoring quinoxaline‐1, 4‐dioxides in feeds. Molecularly imprinted polymers were synthesized in methanol using mequindox (MEQ) as template molecule and acrylamide as functional monomer by bulk polymerization. Under the optimum SPE conditions, the novel polymer sorbents can selectively extract and enrich carbadox, MEQ, quinocetone, and cyadox from a variety of feeds. The molecularly imprinted SPE cartridge was better than nonimprinted, C18, and HLB cartridges in terms of both recovery and precision. Mean recoveries of four quinoxaline‐1, 4‐dioxides from six kinds of feeds spiked at 1.0, 10, and 100 mg/kg ranged between 75.2 and 94.7% with RSDs of less than 10%. The decision limits (CCαs) and the detection capabilities (CCβs) of four analytes were 0.15–0.20 mg/kg and 0.44–0.56 mg/kg, respectively. The class selectivity of the polymers was evaluated by checking three drugs with different molecular structures to that of MEQ.